Magnetic dipole moments of the negative parity $$J^{PC}=2^{--}$$ JPC=2-- mesons in QCD - T. M. Aliev; T. Barakat; M. Savcı (European Physical Journal C: Particles and Fields, 2018)
Abstract Magnetic dipole moments of the negative parity light and heavy tensor mesons are calculated within the light cone QCD sum rules method. The results are compared with the positive parity counterparts of the corresponding tensor mesons. The results of the analysis show that the magnetic dipole moments of the negative parity light mesons are smaller compared to those of the positive parity mesons. Contrary to the light meson case, magnetic dipole moments of the negative parity heavy mesons are larger than the ones for the positive parity mesons.